An immature inhibin‐α‐expressing subpopulation of ovarian clear cell carcinoma cells is related to an unfavorable prognosis. (20th February 2021) - Kusumoto, Shinya; Kurashige, Masako; Ohshima, Kenji; Tahara, Shinichiro; Matsui, Takahiro; Nojima, Satoshi; Hattori, Satoshi; Morii, Eiichi
Abstract: Inhibin‐α, a member of transforming growth factor‐β, is elevated in multiple tumors, but its specific roles are poorly understood. Here, we examined the feature of inhibin‐α‐expressing cells in ovarian tumors. Immunohistochemically, inhibin‐α‐expressing tumor cells were detected only in ovarian clear cell carcinoma (OCCC) among various types of ovarian tumors. By comparing the expression of inhibin‐α and Ki‐67, inhibin‐α‐expressing tumor cells were revealed to be less proliferative. When spheroids and chemoresistant cells were derived from OCCC cell lines, the expression level of inhibin‐α was elevated, and that of an immature marker, aldehyde dehydrogenase, was also elevated. In consistent with this, inhibin‐α expression was correlated with other immature markers, such as OCT3/4 and SOX2, and inversely correlated with proliferative marker MKI67 in public database on OCCC. Knockdown of inhibin‐α in OCCC cell decreased chemoresistance. Moreover, prognostic analysis with 69 surgically resected OCCC cases revealed that the increased inhibin‐α expression was an independent unfavorable prognostic factor. These findings suggested that inhibin‐α‐expressing subpopulation of OCCC tumor cells appeared to be less proliferative, immature, and angiogenic and to be related to acceleration of malignant progression. Abstract : Inhibin‐α‐expressing subpopulation was less proliferative and upregulated in the recurrent site, spheroids and chemoresistant cells. Moreover, those cells had immature properties and high angiogenic potential, leading to unfavorable prognosis